A dynamic management framework for socio-ecological system stewardship: A case study for the United States Bureau of Ocean Energy Management. (1st November 2018) - Auad, Guillermo; Blythe, Jonathan; Coffman, Kim; Fath, Brian D.
Abstract: An effective and efficient stewardship of natural resources requires consistency across all decision-informing approaches and components involved, i.e., managerial, governmental, political, and legal. To achieve this consistency, these elements must be aligned under an overarching management goal that is consistent with current and well-accepted knowledge. In this article, we investigate the adoption by the US Bureau of Ocean Energy Management of an environmental resilience-centered system that manages for resilience of marine ecological resources and its associated social elements. Although the framework is generally tailored for this Bureau, it could also be adapted to other federal or non-federal organizations. This paper presents a dynamic framework that regards change as an inherent element of the socio-ecological system in which management structures, e.g., federal agencies, are embedded. The overall functioning of the management framework being considered seeks to mimic and anticipate environmental change in line with well-accepted elements of resilience-thinking. We also investigate the goal of using management for resilience as a platform to enhance socio-ecological sustainability by setting specific performance metrics embedded in pre-defined and desired social and/or ecological scenarios. Dynamic management frameworks that couple social and ecological systems as described in this paper can facilitate the efficient and effective utilization of resources, reduce uncertainty for decision and policy makers, and lead to more defensible decisions on resources. Highlights: A resilience-based framework is studied for efficient natural resource management. The management framework is expanded and adapted to a specific organization. Nested panarchies are used to couple social and ecological sub-systems. The environmental management framework is used to analyze two practical examples. The management framework could be adapted to other organizations or groups of them.